(untitled) (Edad Media. Revista de Historia, 2017)
Throughout the Late Middle Ages, grief and mourning could be seen as a set of rituals of both political and religious nature, with sorrow in the face of loss as their central element. This paper analyzes the documentation of these rites in the Crown of Castile during the Trastamara period from a specifically political standpoint: the public declaration of treason on the king’s part; the urban protests held against the monarchs in Segovia (1480) and Valladolid (c.1484); the military defeat at the battle of Aljubarrota (1385) and the surrender of Pierres de Peralta, Constable of Navarre, to Pedro Girón, Master of Calatrava (1461), according to the version put forth in Diego Enríquez del Castillo’s Crónica de Enrique IV; and the grief felt at the king’s death. The essay, therefore, highlights the roles played by grief and mourning as key elements in a set of propaganda strategies laid out in a context that put love at the centre of political relations.